Reimagining the Agency of International Students of Color During Global Pandemic and (Neo)Racism - Hou, Minghui (Journal of International Students, 2023)
The global imaginary contributes to the perpetuation of neo-colonial and neo-liberal mentalities, which reinforce the political, cultural, and social dominance over international students. Through an exploration guided by interrelated theories of agency and transnational social fields, this study employs a narrative inquiry methodology with a constructivist research approach to comprehend and investigate the agency of international graduate students of Color amidst transnational mobility during the COVID-19 pandemic within a four-year public research institution in the United States. The research findings demonstrate that specific contexts and spaces shape the agency of international graduate students and (trans)form their present and future. This article reveals four distinct forms of agency: agency as negotiation in uncertainties, agency as resistance to forms of (neo)racism, agency for personal growth and (trans)formation, and agency within transnational futures.